Targeting Epithelial-to-Mesenchymal Transition in Radioresistance: Crosslinked Mechanisms and Strategies - Qiao, Lili; Chen, Yanfei; Liang, Ning; Xie, Jian; Deng, Guodong; Chen, Fangjie; Wang, Xiaojuan; Liu, Fengjun; Li, Yupeng; Zhang, Jiandong (Frontiers in Oncology, 2022)
Radiotherapy exerts a crucial role in curing cancer, however, its treatment efficiency is mostly limited due to the presence of radioresistance. Epithelial-to-mesenchymal transition (EMT) is a biological process that endows the cancer cells with invasive and metastatic properties, as well as radioresistance. Despite many potential mechanisms of EMT-related radioresistance being reported, an overall understanding of the relationship between EMT and radioresistance remains insufficient. In this review, we discuss the interplay between EMT and radioresistance involved in EMT-related mechanisms in regulating radioresistance, irradiation-mediated EMT program, and the intervention strategies to increase tumor radiosensitivity, aiming to improve radiotherapy efficiency and clinical outcomes of cancer patients.